(untitled) (Heritage, 2022)
In this paper the author starts from previous research on the position of the Serbs in Kosovska Mitrovica, whose main part he conducted from 2011 to 2014. Based on the results of this research, the everydayness of the local Serbs, in the changed social-political context in Kosovo and Metohija after the NATO aggression in 1999, the author described as everydayness “captured” in a post-war state of conflict, filled with feelings of threat from Albanians and fear of uncertain tomorrow. Bearing in mind the changes that took place in Kosovo and Metohija after 2011-2014 research, which were initiated by the implementation of the Brussels Agreement, what means by integrating of the institutions of the Republic of Serbia into the institutional system of self-proclaimed independent Kosovo, the author intends to give a contribution to understanding the situation of the Serbs in Kosovska Mitrovica today. He directs the attention to the analysis of the local Serbs attitudes towards the results of the Brussels Agreement, as well as he tries to make an effort to answer the question whether the thesis of the “captured” everydayness of the researched Serbian community is applicable today as it was according to the results of research conducted from 2011 to 2014. The methodological procedure applied in achieving the set goal was based on an anthropologically key perspective, and that is the emic perspective, which means that the author had used the qualitative research approach, primarily the conversation with interlocutors. The results presented in the paper was obtained on the basis of field research conducted in Kosovska Mitrovica during march and april 2022.